Manajemen Laba pada Perusahaan yang Melakukan Agresivitas Pajak - Yantiari, Ni Wayan; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 33 No 1 (2023), 2023)
This research examines the tax aggressiveness of companies with earnings management which reduces earnings before paying taxes. The amount of profit earned will determine the amount of the tax burden paid by the company by imposing a tax rate on profits. The population of research companies listed on the Indonesia Stock Exchange in 2015-2019. From this total population, 103 companies were sampled using the non-probability sampling method with purposive sampling technique. The theory used is positive accounting theory. Data analysis technique used Pearson correlation analysis. The results of data analysis show that there is a significant positive relationship between tax aggressiveness and earnings management. This means that the higher the company performs tax aggressiveness, the higher the tendency of the company to do so with earnings management which reduces profits or in other words there are earnings management actions which reduce profits in companies that carry out tax aggressiveness. Keywords: Tax Aggressiveness; Earning Management; Effective Tax Rate; Discretionary Accrual.